Development of a Framework for Attracting and Retaining Women in Construction Practice - Adogbo, K.J.; Ibrahim , A.D.; Ibrahim, Y.M. (Penerbit Universiti Sains Malaysia, 2015)
Previous research has indicated that women are significantly under-represented in the Nigerian construction industry and that female undergraduates face barriers that deter them from engaging in construction practice. This research examined the barriers faced by female undergraduates in the construction disciplines at Nigerian Universities. The research adopted the use of a questionnaire and semi-structured interviews. A total of 360 questionnaires were distributed, and 259 (71.94%) were returned and used in the analysis. The semi-structured interviews were conducted with 50 female students and 16 women across the professions of Architecture, Building, Civil Engineering and Quantity Surveying. The results revealed that the undergraduates perceived the construction practice to be synonymous with site activities and that family responsibility posed the greatest barrier to their participation. The strategies identified by the women in practice included active participation in the activity of professional bodies and seeking a mentor. It was concluded that female graduates can be attracted to the industry, but efforts need to be put in place to successfully implement the strategies identified by the professional women. A framework that addresses gender issues in attracting and retaining graduates in the construction practice was developed to help women plan their career in the industry.